Budowa kaplicy pw. św. Leonarda w Szczebrzeszynie w świetle źródeł archiwalnych - przyczynek do mecenatu Hrabiego Maurycego Zamoyskiego - Bartko-Malinowska, Anna (Archiwa, Biblioteki i Muzea Kościelne, 2017)
In the cemetery in the town of Szczebrzeszyn, there is a chapel dating from 1907-1908, founded by Count Maurycy Zamoyski, the 15th lord of the Zamoyski Family Fee Tail. This chapel has a long tradition based on the legend about its origins. The present building is the third one standing here, the previous wooden one, from the beginning of the 19th century, was completely destroyed. During the pastoral visit of Bishop Jaczewski in Szczebrzeszyn in 1905, Maurycy Zamoyski promised to rebuild the chapel and to finance the project in its entirety. This was a unique situation because it was rare for any fee tail to cover the cost of the construction of a church. Only materials were usually provided and the aid did not exceed 10% of the collator’s donation. In 1907, Alfons Helbich, the builder of the Fee Tail, started the construction of the chapel designed in Neo-Gothic style; the works were delayed by the government which was reluctant to approve the plans and cost estimates. Therefore, it was necessary for the bishop of Lublin to intervene. The construction was supervised by Michał Kołodziejczyk, a bricklayer, familiar to the Administration of the Fee Tail because he was responsible for the construction of the church in Mokrelipie, also located in the Fee Tail. According to the agreement Kołodziejczyk signed with the Governor of the estate of Zwierzyniec, he was supposed to raise the walls and cover the roof by 1 November 1907, then to finish the chapel and put it into use by 1 June 1908. Kołodziejczyk fully adhered to the agreement, and on 28 November 1908, a protocol of transfer and receipt was signed, in which the chapel was handed over to Rev. Jan Grabarski, a parish priest of Szczebrzeszyn. This chapel is an expression of Count Maurycy Zamoyski’s generosity and his concern for sacred objects in his Fee Tail. This concern is also evidenced by other magnificent churches created during Maurycy’s rule.